Mass spawning aggregation of the giant bumphead parrotfish Bolbometopon muricatum. Issue 1 (25th May 2017) - Roff, G.; Doropoulos, C.; Mereb, G.; Mumby, P. J.
Abstract : The present study reports a previously undocumented mass spawning aggregation and group spawning phenomena of c. 1200 individual bumphead parrotfish Bolbometopon muricatum in Palau, Micronesia. Although B. muricatum are protected in Palau, it is further recommended that management strategies should consider establishment of no‐take zones at B. muricatum spawning aggregations and concomitant sleeping grounds elsewhere.